Menyiapkan Mental yang Tangguh di Masa Transisi menjadi Mahasiswa - Musslifah, Anniez Rachmawati; Anwariningsih, Sri Huning; Cahyani, Rusnandari Retno; Purnomosidi, Faqih (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Mental health is one of the central issues at this time. The importance of every individual, especially adolescents, having mental health is important because adolescents are the successors of the nation who must be resilient in facing all conditions. The purpose of this service is to add insight and a starting point for implementing for new students in preparing a tough mentality in the transition period to become a student. Problems New students are required to be able to adapt quickly. However, it turns out that in the age of freshmen entering the age of late adolescence or early adulthood has problems related to anxiety, so it is not uncommon at that age that teenagers experience an emotional crisis / Quarter-life Crisis. These problems are what hinder teenagers from starting a new life as students in Higher Education. The results of the implementation of good and smooth service activities in the form of seminars with the theme of Preparing a Resilient Mentality in the Transition Period to become Students in new A.K Textile students, as well as increasing the understanding of the participants regarding the Quarter-life Crisis and how to anticipate this